Design of experiment-driven stability-indicating RP-HPLC method for the determination of tofacitinib in nanoparticles and skin matrix - Srividya Gorantla; Ranendra N. Saha; Gautam Singhvi (SpringerOpen, 2021)
Abstract Background Tofacitinib-an oral JAK inhibitor-has been recently approved by US FDA to treat moderate to severe RA. The delivery of tofacitinib to specific inflammation site at joint via topical route using nanoformulations helps in managing the potential adverse effects. The objective is to develop and validate a simple, specific, and sensitive stability-indicating HPLC method for quantification of tofacitinib in topical nanoformulations and different matrices (adhesive tape, and skin layers, i.e., stratum corneum, viable epidermis, and dermis). The major objective was to avoid use of instruments like LC-MS/MS and to ensure a widespread application of the method. Result A 32 factorial 'design of experiments' was applied to optimize process variables, to understand the effect of variables on peak properties. The calibration curve showed regression coefficient (R 2) 0.9999 and linearity in the concentration range of 50 to 15,000 ng/mL, which is suitable for the analysis of conventional dosage forms and nanoformulations. Method validation was performed as per ICH guideline Q2 (R1). The accuracy by recovery studies ranged between 98.09 and 100.82%. The % relative standard deviations in intraday and interday precisions were in the range of 1.16-1.72 and 1.22-1.80%, respectively. Forced degradation studies indicated the specificity of method and showed stability-indicating potential for tofacitinib peak. Conclusion The validated method provides a quantification method of tofacitinib in the presence of formulation excipients, dissolution media, and skin tissues in detail. In addition, the method was successfully utilized for determination of various dermatokinetics profile of tofacitinib.